Examining the Effects of Task-Based Language Teaching and Presentation-Practice-Production Technique on High School Students’ Writing Performance - Lap, Trinh Quoc; Bao Ngoc, Tran Minh; Tuan, Le Cong; Thao, Le Thanh; Khanh Doan, Nguyen Thi (VNU Journal of Science: Education Research; Vol 42 No 1DO - 10.25073/2588-1159/vnuer.5238, 2026)
This study investigates the effects of Task-Based Language Teaching (TBLT) and the traditional approach of Presentation, Practice and Production (PPP) lessons on English writing skills among EFL learners in a high school in Vietnam. With a sample of 80 participants, the study employed a pre-test, middle-test, and post-test design to measure improvements in four aspects of writing: content, organization, vocabulary, and grammar. Both paired-sample t-tests and independent-sample t-tests were used for data analysis. The results revealed that TBLT and PPP significantly improved all aspects of the tested writing. However, TBLT showed more gains, as indicated by higher t-values across the four categories. The study began with no statistically significant differences between the control and experimental groups (p = 0.81). By the middle test, a borderline significance emerged (p = 0.05), indicating that the TBLT intervention may have had an effect. By the post-test, the p-value (p = 0.06) suggested a trend toward improved writing proficiency for the TBLT group. The findings are discussed through the lens of Flow Theory, highlighting the importance of task engagement and intrinsic motivation in the learning process. The study has implications for ELT in Vietnam and similar contexts and offers recommendations for future research.